THE DYNAMICS OF SCARCITY OF ULAMA IN AL JAM'IYYATUL WASHLIYAH NORTH SUMATRA - Rozali, Muhammad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This paper discusses the dynamics of the Al Jam'iyatul Washliyah organization of North Sumatra Indonesia in the past, today and in the future. Al Washliyah is a organization that was born, raised and developed in the city of Medan, inseparable from the influence of the clergy and experiencing various dynamics. The results of this paper are: That Al Wasliyah has great scholars who contribute to providing understanding and enlightenment in the field of religion for the people of North Sumatra. With the age of entering a century, Al Washliyah must be aware of the scarcity of scholars that occur in the midst of its organization. It has become an obligation for Al Washliyah to move quickly to carry out the maintenance of its clerical curriculum if it does not want to be left behind and lose its clerical traditions.